Anonymity, Mutual Disclosure and Trust in Online Counselling Relationships among Students of Obafemi Awolowo University, Ile-Ife, Nigeria - Oluwaseun Solomon Omotehinse; Olusegun Fatai Adebowale (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2020)
The study examined the influence of anonymity and mutual disclosure on trust in online counselling relationships in Obafemi Awolowo University (OAU), Ile-Ife, Nigeria. The study adopted a descriptive survey research design. The population for the study comprised undergraduate and postgraduate students of Obafemi Awolowo University (OAU), Ile-Ife, Nigeria.  Findings revealed that majority of the students showed moderate level of trust. It was also revealed that anonymity (β = 0.310, p < 0.05) and mutual disclosure (β= 0.627, p < 0.05) had positive and significant influence on counsellor-client trust. Also, sex significantly and inversely influenced counsellor-client trust (β= -1.683, p < 0.05), while the type of concerns presented by students had no significant relationship with counsellor-client trust (F= 2.313, p > 0.05).